2015
DOI: 10.1021/acs.energyfuels.5b02059
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Hydrocarbons from High-Maturity Marcellus Shale Using Supercritical Carbon Dioxide

Abstract: Shale is now commonly exploited as a hydrocarbon resource. Due to the high degree of geochemical and petrophysical heterogeneity both between shale reservoirs and within a single reservoir, there is a growing need to find more efficient methods of extracting petroleum compounds (crude oil, natural gas, bitumen) from potential source rocks. In this study, supercritical carbon dioxide (CO 2 ) was used to extract n-aliphatic hydrocarbons from ground samples of Marcellus shale. Samples were collected from vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…Researchers initially explained the influence of mineralogical composition on the reactivity of shales during CO 2 injection. SCCO 2 has high diffusivity and acts as an organic solvent to extract some organic and inorganic minerals, which may lead to an increase in the porosity of shale [55,71]. Previous studies indicated that the alteration in shale mineralogy after SCCO 2 treatment is mainly caused by the geochemical reaction with the formation brine in the presence of carbonate minerals such as dolomite and calcite [18,30,39,43,51,72].…”
Section: Mineral Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers initially explained the influence of mineralogical composition on the reactivity of shales during CO 2 injection. SCCO 2 has high diffusivity and acts as an organic solvent to extract some organic and inorganic minerals, which may lead to an increase in the porosity of shale [55,71]. Previous studies indicated that the alteration in shale mineralogy after SCCO 2 treatment is mainly caused by the geochemical reaction with the formation brine in the presence of carbonate minerals such as dolomite and calcite [18,30,39,43,51,72].…”
Section: Mineral Compositionmentioning
confidence: 99%
“…CO 2 injection causes a reduction in the intensity of C-O bonds in shales as well as aliphatic hydrocarbon (C-H) groups, which is related to the extraction of organic matter [39,71]. Yin et al [30] suggested that some inorganic vibrational bands of quartz and illite (Si-O, Al-O-H and Si-O-Al bonds) can exhibit high absorption in shales similar to calcite and dolomite.…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction efficiency is higher than Soxhlet (Akinlua et al, 2008). These features have been used to evaluate hydrocarbon potential (Jaffé et al, 2000), shale oil development (Wang et al, 2012;Jarboe et al, 2015) and hydrocarbon source rocks (Bondar and Koel, 1998).…”
Section: Extraction Of Organic Components By Supercritical Comentioning
confidence: 99%
“…Some of the dominant, non-aqueous, and widely discussed techniques such as supercritical fluids (SCFs), microwave, and ultrasonic-assisted extraction methods have recently been reported as potential alternatives for unconventional reservoir stimulation applications and extraction of organic fractions from sedimentary rocks. [10,11] These techniques are considered promising for sustainable production compared to hydraulic fracturing due to their reasonable initial and operation costs and because they have low or nonexistent used and produced water, toxic chemicals, seismic alterations, and environmental hazards, which have been determined as more acceptable and have less of an impact on the environment. The applied SCFs are well recognized as self-propping and dissolving agents with improved intensity.…”
Section: Introductionmentioning
confidence: 99%